Seeing is believing: The role of the film Obedience in shaping perceptions of Milgram's Obedience to Authority experiments. (October 2015) - Perry, Gina
Stanley Milgram's film Obedience is widely used in teaching about the Obedience to Authority studies. It is frequently a student's first introduction to Milgram's research and has been a powerful force in establishing the scientific authority of the experiments. This article contextualizes the filming, selection of footage, and final editing of the film against growing ethical and methodological criticisms of Milgram's research. I argue that Milgram's film should be viewed as a response and reply to the criticisms expressed by the National Science Foundation when they refused funding for further experiments. Obedience, the film, originally conceived as a record for future researchers, transformed into a visual document aimed at disarming critics and establishing the universality and profundity of Milgram's findings. Milgram aimed in the film to reconcile the quantitative and the qualitative aspects of the experiments through a scientific narration and footage of participants in action. A close reading reveals that while the film is scientifically unconvincing, and an unreliable account of the Milgram's research, it succeeds spectacularly as arresting and compelling drama.